HUBUNGAN PENINGKATAN BERAT BADAN IBU SELAMA HAMIL DENGAN BERAT BAYI LAHIR LEBIH DI RUMAH SAKIT KHUSUS IBU DAN ANAK SADEWA YOGYAKARTA - Hana Rizka Ananda (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN, 2014)
ABSTRACT One of the most obvious changes in pregnancy is maternal weight gain caused by the growth of the fetus in the womb. Maternal weight gain during pregnancy is used for the development of the fetal body tissues and pregnant women. Effect mothers who has overweight gain during pregnancy is very possible to get overweight baby born. Aim of this research is to determine the relationship of maternal weight gain during pregnancy with overweight baby born in Sadewa Maternity and Children’s Hospital of Yogyakarta. Total of increasing weight mother during pregnancy categorized base on BMI (Body Mass Index) of mother. This study used observational analytic cross sectional. Method to take sampling with simple random sampling, the sample is all mothers who has weight gain during pregnancy who has overweight baby born and normal weight baby born in Sadewa Maternity and Children’s Hospital of Yogyakarta. Period of medical record is August 2009 – September 2013. Hypothesis testing this research using Chi Square test. In this study experienced a weight gain of pregnant women who come into the category up normal by 41 people (55.4%). Overweight baby born ( > 4000 grams ) found as many as 37 people (50%) and the remaining infants of normal weight baby born (2500-4000 g) were found in the same amount as many as 37 people (50%). The result is 0,009 (sig. < 0,05) and p value is 0,335(0,20 – 0,399). It is means that there is a weak relationship between maternal weight gain with overweight baby born in Sadewa Maternity and Children’s Hospital of Yogyakarta. Based on the result above show there is a weak correlation between maternal weight gain with overweight baby born in Sadewa Maternity and Children’s Hospital of Yogyakarta. Key words : weight mother increase during pregnancy with overweight baby born xv